Health Care Professionals on Intermittent Fasting and Their Perspectives - Upadhayay, N. (Devdaha Medical Journal, 2024)
Background: Multiple studies have shown the promising effect of intermittent fasting (IF) in reducing weight, managing blood glucose level, improving cardio-metabolic health, decreasing systemic inflammation and approach for cancer prevention. This study aims to survey why health care professionals (HCPs) are inclined to practice IF. The other objective is to explore the perception and experience of IF among HCPs.Methods: It is a cross-sectional questionnaire based survey. The questionnaire includes open and closed- ended questions regarding knowledge, benefits and side effects; monitoring, perception and experience on IF by HCPs. Data are expressed in frequency and percentage.Results: All HCPs are aware of the process, benefits and side effects of IF. Most of them (11/15) have adopted a balanced diet with 16:8 hour IF schedule. They are inclined towards IF because of its potential benefits for weight reduction and longevity. All of them are satisfied (100%) and 66.67% are happy with the results of IF. It decreased their weight by about 3-5 kg (IF: 3-4 months) to 8-15 kg (IF: 6-10 months), with variability among the participants. IF improved their food behavior, mood, confidence, and aesthetic appearance (7/15). A few participants (2/15) were able to manage their deranged lipid profile. Some of them encountered minimal side effects such as constipation and mild headaches. Lifestyle, work schedule, social gatherings, and family pressure were perceived as major hurdles for sustaining adherence to IF.Conclusion: IF can reduce weight by about 3-5 kg in 3-4 months and 8-15 kg in 6-10 months. IF improves food behavior, elevates mood, enhances well-being, and boosts confidence and body appearance. Flexible scheduling, taking into consideration lifestyle, work schedule, social and family gatherings, may help in sustaining adherence to IF.